STRESSES IN MULTIPHASE EXCAVATION OF TUNELL - Lidija Frgić; Krešimir Tor; Tomislav Hrestak (Rudarsko-geološko-naftni Zbornik, 2003)
Foreseeing of the rock massif behaviour in tunnel breaking out is a complex engineering problem. In projecting it is important to evaluate the stability conditions in excavation and after the acceptance of suitable breaking out methods, the acceptance of supporting in order to stabilize the opening. The New Austrian Tunnel Method (NATM) is the excavation method adaptable to frequent changes of geological and geotechnical conditions at the working face. Beside the excavation of the whole profile, excavations in soft materials along the tunnel trace condition, so called profile development, i. e. the application of multi-phase excavation. The conditions of stresses and strains for the whole-profile excavation are compared with the conditions of stresses and strains for starting stages of multi-phase excavations with the New Austrian Tunnel Method (the paper is published in Croatian).